Mengukur Efektivitas Program Pemberian Makanan Tambahan (PMT) di PAUD: Evaluasi Berbasis Model CIPP - Tumangger, Alfi Mutiara Br; Buulolo, Jultin Kasandra; Siregar, Nurul Amnah; Damayanti, Rizka; Nabila, Sofwatun; Sianturi, Yusri Delfinsta (CV. Eracita Grup, 2025)
The Supplementary Feeding Program (PMT) is an essential initiative implemented in early childhood education settings to support children’s nutritional fulfillment, health awareness, and optimal growth and development. This study aims to evaluate the implementation of the PMT program at Gudiseju Kindergarten using the CIPP Evaluation Model (Context, Input, Process, Product). A mixed-method design was applied, with data collected through observation, interviews, questionnaires, and documentation. Data were analyzed by reviewing the program’s effectiveness based on the four components of the CIPP model. The findings reveal that the context component achieved a score of 88%, indicating that the PMT program is highly relevant to the needs of the children and aligned with institutional goals. The input component was categorized as good, although improvement is required regarding standardized menu planning and collaboration with nutrition specialists. The process component also showed good results, characterized by structured implementation despite the absence of systematic monitoring documentation. The product component achieved a score of 70%, suggesting positive changes in children’s eating habits, although improvement is not yet evenly distributed. Overall, the PMT program can be categorized as successful; however, further enhancements are needed in planning, implementation supervision, and structured evaluation procedures. This study is expected to serve as a reference for other early childhood education institutions in improving PMT program implementation to support better nutritional and health outcomes for young children.